PROSES PENGADAAN BARANG DAN JASA OLEH PEMERINTAH DAERAH (SUATU STUDI DI PROVINSI BALI) - Sanjayadiputra, Ida Bagus Nyoman; Tjukup, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Title of this paper is Provisioning Proccess Asset of Region Government whichis the research in Bali Province that caused by the policy of and strategy toprovisioning asset so they can make some disclipine in administration and alsodisclipine in managing region asset. The problems are what is the main foundation ofmanaging regulation and provisioning proccess of asset Region Government in BaliProvince and also what is the problem in provisioning asset in Region Goverment ofBali Province. The method of this research is the empirical method with regulations andconseptual approach, meanwhile the technique to collect all data used article tracingand then analysed with quantitatif proccess. The result of analysed are provisioningasset in Region Government of Bali Province have matched with the own regulations,but the reality had many problem. The result is managing and provisioning proccessasset, Governmet of Bali Province using Peraturan Presiden Nomor 54 Tahun 2010about provisioning asset in Government, meanwhinle the problem are less of skill,experience and ability the people who mixed up with in provisioning asset in proccess toprovide them.
Keywords: Provisioning asset, Region Governement, Bali Province